A system for computer aided processing of phonetic measurements - Holtse, Peter (Annual Report of the Institute of Phonetics University of Copenhagen, 1976)
A set of computer programs is described which will sample and average e.g. intonation, air pressure, or EMG activity. Data processing is essentially user controlled, but trivial decisions may be left to the computer if this is desired. The programs are accessible to users with little experience with computers.